Implementasi kedalaman spiritual dan keagungan akhlak mahasiswa UIN Malang melalui kegiatan Taklim Afkar Mahad - Assabti, Zalaludin (Maliki Interdisciplinary Journal, 2023)
Implementation in general can be interpreted as the realization of a thought in real life. A good thought will produce good activities or activities when the thought is carried out. The UIN Maulana Malik Ibrahim Malang campus is the first and only campus that implements the mahad curriculum in an orderly manner, as well as making mahad one of the distinctions owned by the UIN Malang campus. Spiritual depth and moral majesty are two of the pillars of ulul albab on the UIN Maulana Malik Ibrahim Malang campus. This university has 4 pillars of which the remaining two are breadth of knowledge and professional maturity. Taklim afkar, which is a learning activity at Mahad Sunan Ampel Al-Aly based on fiqh and adab. This taklim study uses the books of Tadzhib and Qomi' Thugyan. For mahasantri this activity must be followed as an absolute requirement to be able to graduate mahad.